Flow Characteristics of Pumps in Series and Parallel - Lesmana, Pandu; Nuramal, Agus; Suryadi, Dedi (UNIB Press, 2021)
Pump is a device used to move fluid. The pump moved the fluid from a lower pressure place to a place with higher pressure. If the head or pump capacity needed cannot be achieved using only one pump, it can use two pumps or even more which can be arranged either in series or in parallel. The research objective for pumps arranged in series and in parallel is to determine the characteristics of the circuit of two pumps each of which has different characteristics. In this study, data retrieval is done by measuring the pressure on suction and discharge using pressure gauge at pumps 1 and 2. Whereas to measure the flow rate of a pump arranged in series and parallel using a flowmeter installed on the discharge side of the circuit. This research was done by varied the valve openings on the pump discharge side 2 namely. 2x1800, 4x1800, 6x1800, 8x1800 and full openings. From the results of tested the characteristics of the pump used water fluid on the series arrangement, the highest head value at valve opening 2 x 1800 is 30.99 m at discharge 0 LPM and the lowest head at valve opening 10 x 1800 (full) is 23.99 m at discharge 0 LPM. In parallel circuits, the highest head obtained is 16.99 m with 0 LPM discharge at 8 x 1800 valve openings and lowest head 14.99 at 0 LPM discharge occurs at full valve openings.